A COMPREHENSIVE EXAMINATION OF GENDER DISCRIMINATION AND EMPLOYEE PERFORMANCE AMONG ACADEMIC FACULTY IN HIGHER EDUCATION INSTITUTIONS - Keshari, Anushka; Singh, Pooja; Chaubey, Diksha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Research conducted within colleges in the Varanasi district highlights the crucial significance of implementing gender-neutral recruitment policies to bolster employee performance, aligning with established scholarly discourse on organizational behavior. Despite persistent challenges posed by gender discrimination across various societal dimensions, this study specifically delves into the impact of gender-based discrimination against women on job performance within government universities situated in a distinct geographic region. Employing a methodological framework tailored to the research context, a dataset comprising 107 meticulously completed questionnaires was assembled from academic personnel within government-affiliated universities and colleges in the specified region. Employing sophisticated statistical methodologies such as Pearson correlation and regression analysis, the study discerns a discernible negative correlation between instances of gender-based discrimination in managerial capacities and subsequent job performance outcomes. These findings underscore the deleterious ramifications of gender bias on organizational effectiveness and advocate ardently for the adoption of meritocratic principles in staffing decisions across university settings. Applying these insights to the collegiate landscape of the Varanasi district accentuates the imperative of addressing gender-based discrimination as a strategic imperative to optimize institutional performance and cultivate inclusive organizational cultures conducive to academic excellence.